Investigation of the anti-inflammatory effect of Curcuma longa in Helicobacter pylori-infected patients - Koosirirat C. (2017)
Helicobacter pylori infection of the lining of the stomach induces an array of inflammatory cytokine production leading to gastritis and peptic ulcer disease. The aim of this study was to investigate the effect of curcumin on the production of interleukin (IL)-8, IL-1β, tumor necrosis factor (TNF)-α and cyclooxygenase (COX)-2 in gastric mucosa from H. pylori-infected gastritis patients. Patients were randomly assigned to receive either OAM (Omeprazole, Amoxicillin and Metronidazole) treatment or a course of curcumin. Gastric biopsies were collected before and after treatment and were examined for the level of inflammatory cytokines mRNA by semi-quantitative reverse transcription polymerase chain reaction. The eradication rate of H. pylori in patients that received OAM treatment was significantly higher than the patients that received curcumin (78.9% versus 5.9%). The levels of IL-8 mRNA expression in the OAM group significantly decreased after treatment, but no changes of other cytokines were found. This emphasizes an important role of IL-8 in H. pylori infection. The decreases of cytokine production were not found in the curcumin group. We concluded that curcumin alone may have limited anti-bactericidal effect on H. pylori, and on the production of inflammatory cytokines. Nevertheless, other studies have reported that patients treated with curcumin had relieved symptoms. Further investigation should be carried out as the use of curcumin in combination with therapeutic regimens may be beneficial as an alternative treatment. © 2010 Elsevier B.V. All rights reserved.